ANALISIS KESULITAN SISWA KELAS IV SEKOLAH DASAR DALAM MENYELESAIKAN SOAL PEMECAHAN MASALAH - Sajaâ€™ah, Ummu Fauzi (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2018)
Abstract:. One of the goals of mathematical education is for students to have the ability to solve problems that include the ability to understand problems, design math models, complete the model and interpret the solutions obtained. So that students are expected to solve the problems that they encounter in their daily lives. However, difficulties can not be avoided when students are faced with the problems they encountered. The purpose of this study is to explain 1) Student difficulties in completing problem-solving question based on Polya's approach; 2) The cause of student difficulty in completing problem solving. Research method used is descriptive qualitative research method. The subject of this research is the fourth grade students in one elementary school in West Bandung Regency with a total of 30 students. Once analyzed, the results obtained are that students are having difficulty at 1) Determining the way in which the solution should be done to solve the problem; 2) Perform correct count operation 3) Conclude from result obtained.Â Abstrak: Salah satu dari tujuan pendidikan matematika adalah agar siswa memiliki kemampuan untuk memecahkan masalah yang meliputi kemampuan memahami masalah, merancang model matematika, menyelesaikan model dan menafsirkan solusi yang diperoleh. Sehingga siswa diharapkan mampu menyelesaikan permasalahan yang ia temui dalam kehidupan sehari-hari. Namun, kesulitan-kesulitan tidak dapat dihindari ketika siswa dihadapkan pada persoalan yang ia temui. Tujuan dari penelitian ini adalah untuk menjelaskan 1) Kesulitan-kesulitan siswa dalam menyelesaikan soal pemecahan masalah berdasarkan langkah menurut Polya; 2) Penyebab kesulitan siswa dalam menyelesaikan soal pemecahan masalah. Metode penelitian yang digunakan adalah metode penelitian kualitatif deskriptif. Subjek dari penelitian ini adalah siswa kelas IV di salah satu SD di Kabupaten Bandung Barat dengan jumlah siswa 30 orang. Setelah dianalisis, hasil yang diperoleh bahwa siswa mengalami kesulitan pada 1) Menentukan cara penyelesaian yang seharusnya dilakukan untuk menyelesaikan soal tersebut; 2) Melakukan operasi hitung secara benar 3) Membuat kesimpulan dari hasil yang telah diperoleh.